2011
DOI: 10.1021/jo201645t
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement of Aryl- and Benzylthiopyridinium Imides with Participation of a Methyl Substituent

Abstract: 6-Methyl substituted 2-aryl- and 2-benzylthiopyridinium N-imides reacted with an excess of isocyanates to give N,N-disubstituted exocyclic1H-imidazo[4,5-b]pyridin-2(3H)-ones. The products easily underwent spontaneous [1,5] hydrogen shift to provide the heteroaromatic imidazopyridinone isomers. The transformation implied the initial formation of [1,2,4]triazolo[2,3-a]pyridinium salt, followed by deprotonation and carbamoylation of the methylene moiety, and, finally, a rearrangement following a [1,3] sigmatropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Intramolecular reaction of 2-(2-alkynyl)anilines under the above conditions gave access to 2-substituted indoles . Imidazole-2-thione core is a key structural component of several bioactive molecules, and large numbers of synthetic approaches have been reported for the formation of this core . But synthesis of imidazole-2-thiones by hydroamination reaction of propargylamine remains an unexplored field.…”
mentioning
confidence: 99%
“…Intramolecular reaction of 2-(2-alkynyl)anilines under the above conditions gave access to 2-substituted indoles . Imidazole-2-thione core is a key structural component of several bioactive molecules, and large numbers of synthetic approaches have been reported for the formation of this core . But synthesis of imidazole-2-thiones by hydroamination reaction of propargylamine remains an unexplored field.…”
mentioning
confidence: 99%
“…The NMR peak assignments were performed on the basis of one-( 1 H, 13 C NMR) and two-dimensional ( 1 H− 13 C-gHSQC, 1 H− 13 C-gHMBCAD) experiments. The coherence transfer delays in the 1 H− 13 C-gHSQC measurements were set to 1 / 4 J, where the one-bond J coupling was 140 Hz.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Recently we have found that arylsulfanopyridinium amidates ( 1 ) as reactive mesomeric betaines can serve as valuable starting materials for 1,3-dipolar cycloadditions and subsequent transformations. Thus, syntheses of triazolo­[2,3- a ]­pyridinium salts, pyrrolo­[3,2- b ]­pyiridines, imidazo­[4,5- b ]­pyridines, 4-azaindoles, , and 7-azaindoles have been elaborated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2-Aminopyridine/amidine has long been realized as one of the most widely used commercial reagents in organic synthesis. In the past few decades, the 2-aminopyridines acted as a directing group providing a basic block for the elegant construction of five- or six-membered nitrogen-containing heterocyclic compounds by the formation of N–C, N–N, and N–O bonds . In 2013, our group also developed an efficient method for the synthesis of 2-haloimidazopyridines from aminopyridines and haloalkynes under a Cu/O 2 catalytic system, in which bidental nitrogen atoms of 2-aminopyridine might coordinate with Cu and then activate another substrate (Scheme ).…”
Section: Introductionmentioning
confidence: 99%